Conventional casein phosphopeptide-amorphous calcium phosphate Versus casein phosphopeptide-amorphous calcium phosphate with nanosilver Particles On Primary Canine's Enamel Microhardness: CPP-ACP Vs. CPP-ACPAg On Primary Canine's Enamel Microhardness - kooshki, Fahimeh; Mahmoodabadi, Mehrnaz; Karimi, Samin (Journal of Dental School, 2023)
Objectives: Due to the importance of using more effective varnishes to prevent dental caries, this study aimed to compare the effect of conventional casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and CPP-ACP with 1 and 2 w% nanosilver particles on microhardness of enamel of primary canines. Methods: The initial surface micro-hardness of 36 intact human deciduous canines were measured by a Vickers hardness tester, then samples were immersed in demineralization solution for 24 hours, and then the microhardness of samples was re-measured. All samples were randomly divided into 4 groups (n=9): (A) control group(without therapy), (B) conventional CPP-ACP, (C) CPP-ACP with 1% nano silver, and (D) CPP-ACP with 2% nanosilver. Then samples were entered into pH cycles for 7 days. At the end of pH cycling, the surface microhardness of samples was measured, and the mean for each group was calculated. Data analysis was performed using one-way ANOVA and Tukey analysis. Results: The mean enamel micro-hardness in all groups after demineralization decreased significantly (P<0.05), but this reduction was significantly less in all three experimental groups compared to the control group (P<0.05). There was no significant difference in the rate of surface microhardness changes between the three experimental groups (P>0.05). Conclusion: Conventional CPP-ACP and CPP-ACP with 1 and 2 w% Nanosilver particles were equally effective on the enamel surface microhardness of human deciduous teeth. Silver Nanoparticles have no negative effect on enamel microhardness.